EFFECTS OF VITAMIN D3 LEVELS ON GROWTH AND SURVIVAL RATE OF SNUBNOSE POMPANO JUVENILE (Trachinotus blochii Lacepède, 1801) - Hung, Lai Van; Thu, Huynh Thu; Dung, Tran Van; Trang, Tran Thi Le; Khanh, Pham Thi (Vietnam Journal of Marine Science and Technology, 2014)
Vitamin is one of the most important nutrient components having strong effects on growth, survival rate and food conversion ratio in marine finfish in general and in snubnose pompano in particular. In this study, 3 levels of vitamin D3 (100, 115 and 130mg/kg dry feed) and a control treatment (0mg/kg dry feed) were tested in order to evaluate the effects of this component in diets on growth, survival rate and food conversion ratio in rearing the snubnose pompano juveline. Results showed that the level of 130mg/kg dry feed gave higher specific growth rate of body weight and final weight gain (0.89%/day; 11.29%/day; 11.18g/ind.) compared to the rest vitamin D3 levels (p < 0.05). Apart from the specific growth rate of total length, the fish were fed on diets contained vitamin D3 100 and 115mg/kg dry feed obtained higher specific growth rate of body weight and final weight gain compared to those of the control treatment (9.74%/day; 9.36g/ind. and 10.53%/day; 10.09g/ind. as opposed as 6.43%/day; 7.28g/ind.; p < 0.05). There were no significant differences about these parameters between the treatments of 100 and 115mg/kg dry feed. However, the supplement of vitamin D3 in diets had no significant effects on food conversion ration (1.17 - 1.41) and survival rate (91.95 - 96.67%). From the results of this study, it can be suggested that the appopriate level of vitamin D3 supplement should be 130mg/kg dry feed to optimize the growth of the pompano juveline.